Presenting of executable model of the enterprise architecture in order to evaluate the reliability (International Journal of Engineering and Computer Science, 2014)
In this study has been used unified modeling language and reliability parameter as generalize stereotypes have been added. Then, executable model of enterprise architecture products has been made by using Colored Petri Net. By using the results of simulation of this model we can compute the minimum and maximum of reliability (interval of reliability). The proposed approach than former methods has this privilege that by early computing of reliability in planning phase and consider the feedback on the model and modify the model, it is possible to avoid onerous costs of implementation.